Use of backboards in cardiopulmonary resuscitation: a systematic review and meta-analysis. (June 2021) - Paganini, Matteo; Mormando, Giulia; Carfagna, Fabio; Ingrassia, Pier Luigi
Abstract : To achieve optimal chest compression depth, victims of cardiac arrest should be placed on a firm surface. Backboards are usually placed between the mattress and the back of a patient in the attempt to increase cardiopulmonary resuscitation (CPR) quality, but their effectiveness remains controversial. A systematic search was performed to include studies on humans and simulation manikins assessing CPR quality with or without backboards. The primary outcome of the meta-analysis was the difference in chest compression depth between these two conditions. Out of 557 records, 16 studies were included in the review and all were performed on manikins. The meta-analysis, performed on 15 articles, showed that the use of backboards during CPR increases chest compression depth by 1.46 mm in manikins. Despite statistically significant, this increase could have a limited clinical impact on CPR, due to the substantial heterogeneity of experimental conditions and the scarcity of other CPR quality indicators. Abstract : Supplemental Digital Content is available in the text.